Предмет: Алгебра,
автор: Marloyk
Упростите выражение
1) √2 sin (п/4+a) - cos a
2) √2 sin (a-п/4) - sin a
3) 2 cos (п/3-a) - √3 sin a
4) √3 cos a - 2 cos (a-п/6)
Ответы
Автор ответа:
0
1. = √2 sin cos a + cos sina - cos a = √2 cos a + sina - cos a = cos a + sina - cos a = sin a
2. = √2 cos sina - sin cos a = sin a + cosa - sin a = - cos a
3. = 2 ( cos cos a + sin sin a) - √3 sina = 2 ( cosa + sina) - √3 sina = cosa + √3 sina - √3 sina = cosa
4. = √3 cosa - 2 ( cos cos a + sin sin a) = √3 cosa - 2 ( cosa + sina ) = √3 cosa - √3 cosa - sina = - sina
2. = √2 cos sina - sin cos a = sin a + cosa - sin a = - cos a
3. = 2 ( cos cos a + sin sin a) - √3 sina = 2 ( cosa + sina) - √3 sina = cosa + √3 sina - √3 sina = cosa
4. = √3 cosa - 2 ( cos cos a + sin sin a) = √3 cosa - 2 ( cosa + sina ) = √3 cosa - √3 cosa - sina = - sina
Похожие вопросы
Предмет: Математика,
автор: romansdv96
Предмет: Русский язык,
автор: zumabaevasamara57
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: zutava
Предмет: Биология,
автор: godlovesugly